2015
DOI: 10.1186/s13049-015-0099-x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency surgery in the elderly: the balance between function, frailty, fatality and futility

Abstract: Becoming old is considered a privilege and results from the socioeconomic progress and improvements in health care systems worldwide. However, morbidity and mortality increases with age, and even more so in acute onset disease. With the current prospects of longevity, a considerable number of elderly patients will continue to live with good function and excellent quality of life after emergency surgical care. However, mortality in emergency surgery may be reported at 15-30%, doubled if associated with complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
2
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 49 publications
0
48
2
6
Order By: Relevance
“…But of greatest importance are age and comorbidity, both strongly associated with long-term deterioration due to frailty in the elderly, and both strongly associated with short and long-term mortality after surgery. 11,12 Frailty is a lack of resilience to stressors to physiological systems. Although there might be survival of the initial insult, the challenge to the body and organ systems may reveal previously unrecognised organ failure or trigger new physiological weakness.…”
Section: Scandinavia Survival and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…But of greatest importance are age and comorbidity, both strongly associated with long-term deterioration due to frailty in the elderly, and both strongly associated with short and long-term mortality after surgery. 11,12 Frailty is a lack of resilience to stressors to physiological systems. Although there might be survival of the initial insult, the challenge to the body and organ systems may reveal previously unrecognised organ failure or trigger new physiological weakness.…”
Section: Scandinavia Survival and Mortalitymentioning
confidence: 99%
“…17 The rate of high-risk patients with preexisting comorbidities is increasing in high-income countries and is related to demographic changes. 3,11 Adaptations of postoperative surveillance management are imperative, but may not need expensive ICU beds. Identification of index markers that trigger a priority for a higher level of care, IMC or ICU level, are needed.…”
Section: Scandinavia Survival and Mortalitymentioning
confidence: 99%
“…Most probably this is related to the degree of severity of the patient at admission. Elderly people represent a heterogeneous group of patients, ranging from very fit to very frail individuals consequently with decreased physiological reserves, due to chronological age and biological changes, making these patients vulnerable to any stressful event [8][9] . There is a lack of studies evaluating early and late outcomes of emergency abdominal surgery in the cohort of patients aged over ninety years affected by colorectal cancer.…”
Section: Emergency Abdominal Surgery For Crc In Elderly:diagnosis Andmentioning
confidence: 99%
“…Recent retrospective studies [8] demonstrated that high ASA class is associated with high mortality following emergency surgery.…”
Section: Emergency Abdominal Surgery For Crc In Elderly:diagnosis Andmentioning
confidence: 99%
“…This vulnerability to a stressful event has been suggested as a risk predictor and is associated with substantial morbidity and mortality [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%